The effect of breakthrough pain on heart and lung function during the cancer pain treatment in palliative care (Journal of Health Sciences, 2011)
Introduction: The aim of the research was to determine the effect of breakthrough pain (BTP) on heart and lung function in patients whose cancer pain had been treated with strong opiates.Methods: A prospective study was conducted on 80 patients who were treated in recumbent patients’ hospice of Palliative Care Centre (hospice) University Clinical Centre Tuzla. The effect of pain breakthrough onheart function was monitored by blood pressure and pulse measuring outside. The effect on respiratory function was monitored by measuring the respiration number with SpO2 and pCO2 and pO2 capillary blood valuesoutside, during and after relieving pain breakthrough.Results: Mean value for Karnofsky score for patients upon admission was 47.13 ± 11.05 and on discharge 51.25 ± 11.73. The total number of pain breakthroughs for patients within the 10 days of the treatment was1396. During the pain breakthrough the mean of systolic pressure was 133.1 mmHg and it was statistically significantly higher than the mean of systolic pressure measured after BTP relief with oral morphine. Themean of diastolic pressure measured outside of pain breakthrough was 75.9 mmHg and after the BTP relief it was 72.9 mmHg. The mean pulse outside of pain breakthrough was 92.7 heartbeats per minute and afterthe BTP relief 8 9.1 heartbeats per minute.Conclusion: Pain breakthrough leads to pulse acceleration, increased systolic and diastolic blood pressure and it also affects respiratory function by accelerating the respiration